KESIAPAN SISWA DALAM MENYELESAIKAN SOAL ASESMEN KOMPETENSI MINIMUM (AKM) LITERASI DAN NUMERASI KELAS V SDN PALEBON 1 SEMARANG (JS (JURNAL SEKOLAH), 2022)
Abstract: Student Readiness in Completing the Literacy and Numeracy Minimum Competency Assessment (AKM) for Class V SDN Palebon 1 Semarang. The purpose of this study is to find out how the level of readiness and difficulty of class V students in solving AKM literacy and numeracy problems. Data collection techniques used in research are questionnaires, interviews, test, and documentation. The data source used in this study were 10 students of class V, where the results of this study are the level of readiness of class V students in solving AKM literacy and numeracy problems from internal factors that include intelligence, talent, interest, motivation, and physical and spiritual health of students, which is 51% with the category "sufficient", while from external factors that include the family environment, which is 49% with the category "sufficient". Based on the results of the analysis of literacy and numeracy tests, the average student gets a score below KKM. In the problem of literacy tests the highest score obtained by students is 56.6 "enough" and the lowest score obtained by students is 10.5 "very less". While in the matter of numeracy test the highest grade obtained by students is 43 "enough" and the lowest score obtained by students is 18 "very less". Based on interviews conducted with students, the readiness level criteria of students of class V SDN Palebon 01 Semarang are 20% of students with "excellent" readiness level categories, 20% of students with "good" readiness level categories, 50% of students with "sufficient" readiness level categories, while 10% of students with "low" readiness level categories.Keywords: Minimum Competency Assessment, Readiness, Literacy and Numeracy.  Abstrak: Kesiapan Siswa Dalam Menyelesaikan Soal Asesmen Kompetensi Minimum (AKM) Literasi Dan Numerasi Kelas V SDN Palebon 1 Semarang.  Tujuan dari penelitian ini adalah untuk mengetahui bagaimana tingkat kesiapan siswa kelas V dalam menyelesaikan soal AKM literasi dan numerasi. Teknik pengumpulan data yang digunakan dalam penelitian adalah angket, wawancara, soal tes, dan dokumentasi. Sumber data yang digunakan dalam penelitian ini adalah 10 siswa kelas V, dimana hasil penelitian ini adalah tingkat kesiapan siswa kelas V dalam menyelesaikan soal AKM literasi dan numerasi dari faktor internal yang meliputi intelegensi, bakat, minat, motivasi, serta kesehatan jasmani dan rohani siswa yaitu 51% dengan kategori œcukup, sedangkan dari faktor eksternal yang meliputi lingkungan keluarga yaitu 49% dengan kategori œcukup. Berdasarkan hasil analisis soal tes literasi dan numerasi, rata-rata siswa mendapatkan nilai di bawah KKM. Pada soal tes literasi nilai tertinggi yang diperoleh siswa yakni 56,6 œcukup dan nilai terendah yang diperoleh siswa yakni 10,5 œsangat kurang. Sedangkan pada soal tes numerasi nilai tertinggi yang diperoleh siswa yakni 43 œcukup dan nilai terendah diperoleh siswa yakni 18 œsangat kurang. Berdasarkan wawancara yang dilakukan dengan siswa, kriteria tingkat kesiapan siswa kelas V SDN Palebon 01 Semarang yaitu 20% siswa dengan kategori tingkat kesiapan œsangat baik, 20% siswa dengan kategori tingkat kesiapan œbaik, 50% siswa dengan kategori tingkat kesiapan œcukup, sedangkan 10% siswa dengan kategori tingkat kesiapan œrendah. Kata Kunci: Asesmen Kompetensi Minimum, Kesiapan, Literasi dan Numerasi.